Synthesis of Luminescent Ink from Europium-Doped Y2O3 Dispersed in Polyvinyl Alcohol Solution. (3rd May 2009) - Astuti,; Abdullah, Mikrajuddin; Khairurrijal,
Abstract : Luminescent ink from europium-dopedY 2 O 3 (Y 2 O 3 :Eu) has been synthesized by two steps method: first, synthesis of luminescent powder ofY 2 O 3 :Eu by simple heating of metallic nitrates in a polymer solution and second, dispersing the powder in a polyvinyl alcohol (PVA) solution. The stability of the ink (luminescent colloid) was strongly affected by mixing process of the powder and the solution. Mixing process must be performed for a long time (about 8 hours) at above room temperature to product stable colloids. We observed that mixing at 30–40 ∘ C resulted in a stable and highly dispersed colloid. The writing test was performed on a white paper to show the potential use of the colloid for making security codes.